بناء الحوار والشخصية في القصة القصيرة الجزائرية قصة ( الحصاد) لفاطنة الباي - نموذجا - زهرة جغبالة; زينب زايد; شمس الأصيل ثامر; زعفاف خزان (جامعة الوادي - University of Eloued, 2025)
يتضمن بحثنا فصلين الفصل الاول نظري وفيه تطرقنا الى القصة القصيرة(مفهومها٫ ارهاصاتها، نشاتها، روادها، اتجاهاتها، اسباب تاخرها في الجزائر) وتطرقنا ايضا إلى الركائز الفنية للقصة القصيرة في الجزائر وتعريف الشخصية وانواعها وتعريف الحوار واهميته داخل النص الادبي وانواعه. اما في الجزء التطبيقي تضمن جماليات الشخصية والحوار في قصة الحصاد لفاطنة الباي ،حيث تعرضنا فيه الى دراسة تحليلية(مظاهر الحوار والشخصية وابعادها، مظاهر الحوار، المظاهر اللغوية والفكرية في القصة القصيرة، الرؤية السردية)وتوصلنا الى اهم النتائج الاتية: _ان اهم ركائز القصة(الوحدة، التكثيف، الدراما) _تتنوع الشخصيات في قصة( الحصاد)من شخصيات رئيسية واخرى ثانوية واخرى هامشية._ _استعملت الكاتبة الحوار الداخلي، ووظفت الحوار الخارجي. Our research includes two chapters. The first is theoretical and addresses the short story (its concept, its precursors, its origins, its pioneers, its trends, and the reasons for its late arrival in Algeria). We also address the artistic foundations of the short story in Algeria, the definition of character and its types, and the definition of dialogue, its importance within a literary text, and its types. The applied section includes the aesthetics of character and dialogue in Fatina Al-Bay's story "The Harvest." We conducted an analytical study (the aspects of dialogue and character and their dimensions, aspects of dialogue, linguistic and intellectual aspects in the short story, and narrative vision). We arrived at the following important conclusions: The most important foundations of the story are (unity, condensation, and drama). The characters in the story "The Harvest" vary from main characters to secondary and marginal characters. The author uses internal dialogue and external dialogue.
مذكرة ليسانس. دراسات أدبية
Keywords: الحوار، الشخصية، القصة القصيرة، الرؤية السردية; Dialogue; character; short story; narrative vision.